Food Consumption Pattern and Dietary Diversity in Nepal: Implications for Nutrition Security. Issue 3 (December 2016) - Kumar, Anjani; Kumar, Praduman; Joshi, P. K.
This article examines the status, progress and challenges of managing food and nutrition security in Nepal, one of the least developed countries, by using data from the national living standards surveys conducted jointly by Government of Nepal and World Bank. Nepal, like many other developing countries, is struggling to ensure food and nutrition security. This study analyses the dimensions of food security in terms of availability, access and utilization (nutritional outcome). The analysis shows that the trends in food consumption pattern and nutritional intake have changed significantly overtime. The diversity in dietary pattern has become more apparent over time and the dietary diversity depicts a positive impact on nutritional outcome.